Continuous glucose monitoring system can improve the quality of glucose control and glucose variability compared with point-of-care measurement in critically ill patients: A randomized controlled trial. Issue 36 (September 2018) - Lu, Meizhu; Zuo, Yanyan; Guo, Jun; Wen, Xiaoping; Kang, Yan
Abstract: Background: The purpose of this study was to determine whether subcutaneous continuous glucose monitoring systems (CGMS) could improve glucose management in critically ill patients compared with frequent and conventional point-of-care (POC) glucose measurements. Methods: A total of 144 patients with an expected length of stay in the ICU of at least 72 hours and with an admission glucose or two random glucose values of >10.0 mmol/L within 24 hours after admission, were randomly assigned to the CGMS group (n = 74) or the conventional group (C group, n = 70). Both groups used the same insulin algorithm to reach the same glucose target range (8.0–10.0 mmol/L). Results: Time in range (TIR, 8.0–10.0 mmol/L), which is our primary outcome measure, was higher in the CGMS group than in the C group (51.5% vs. 29.0%, P  < .001). Glucose variability (coefficient of variation, CV; standard deviation, SD; glucose lability index, and GLI) was improved by CGMS (all P  < .05). Mean glucose level (MGL) (9.6 vs. 10.3 mmol/L, P  = .156) and the proportion of patients with hypoglycemia did not differ between CGMS (5.4%) and C (5.7%) ( P  = 1.000). However, duration of hypoglycemia was reduced in the CGMS group (15 vs. 28 minutes, P  = .032). Clinical outcomes were similar between groups except for the fewer usage of CRRT and lower peak plasma urea nitrogen level in the CGMS group. Conclusion: The use of CGMS, compared with POC glucose measurement, could improve the TIR, GV and duration of hypoglycemia. Abstract : Supplemental Digital Content is available in the text